INTERNATIONAL STANDARDS OF ACCOUNTING AND REPORTING AS A NECESSITY FOR ACCOUNTING SUPPORT OF AGRICULTURAL ENTERPRISES IN CURRENT CONDITIONS - Tsitska Н.; Myronchuk З.; Tsitskyi П.; Maletska О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The research is aimed at solving the problem of justifying the feasibility of introducing IFRS (International Financial Reporting Standards) into the production practice of agricultural enterprises. The content, purpose, and composition of international financial reporting and accounting standards are highlighted. The existing theoretical, methodological, organizational and practical provisions and recommendations for the organization of accounting through the application of IFRS in agricultural enterprises are considered. The main aspects of the development of international accounting standards in the world and their phased implementation in Ukraine are highlighted. The compliance with IFRS in the global space in the current conditions, as well as the dynamics of their implementation at the national level are analyzed. The stages of transition to IFRS by enterprises that are obliged to comply with them following the current legislation are investigated. The authors substantiate and prove the expediency of organizing accounting support for the economic activities of Ukrainian agricultural producers under international financial reporting standards to achieve effective management of their activities, attract foreign investment and strengthen their competitiveness in international markets in the context of European integration processes in the war and post-war periods. As one of the arguments for the demand for international reporting standards in the organization of accounting at agricultural enterprises, the author provides the number of direct losses incurred during the full-scale invasion by individual industries and agro-industrial complex. A step-by-step procedure has been developed, i.e. an algorithm that should be followed when transforming accounting support to IFRS.